PROGRAMA "CHOCÓ BIOGEOGRÁFICO" MARCO DE REFERENCIA (2013)
In 1994 Pizano S.A. and Pontificia Universidad Javeriana signed up a cooperation agreement in order to develop technical and scientific research áctivities in forest exploitation zones. Asan initial step, the "Chocó Biogeografico" program was created, which includes the project "Biodiversity ofwood exploitation areas belonging to Pizano S.A. in the choco Region". This program is being developed by Unidad de Ecología y Sistemática (UNESIS) (Departrnent of Biology) at Pontificia Universidad Javeriana. One graduate and eleven undergraduate biology thesis are also being carried on in severa! ecological fea tu res in this region. This paper presents the main purposes and conceptual basis of the program.